(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Objectives: To find out the incidence, distribution, level and staging of cervical nodal metastasis. Methods: This is a retrospective study carried out in the Department of Otolaryngology Head and Neck Surgery, BSMMU and Dhaka Medical College Hospital, Dhaka, from January 2005 to December 2005. Total 60 cases were studied. The diagnosis was made by detailed history, clinical examination, investigation. Analyzed data presented by various tables, graphs and figures. Results: In this study primary lesion was identified in 88.33% cases and undetected cases were 11.7%, 81.13% were squamous lining and 18.87% non-squamous. Highest frequency of metastatic node was found with carcinoma larynx (36.66%). Male and age of 41-50 years was had highest incidence. About 43.33% had dysphagia, 38.33% had hoarseness of voice, 13.33% respiratory distress, 8.33% strider and 8.33% had referred otalgia. The disease was unilateral 81.67%, 63.33% multiple node involvement, highest involvement in level II & III and stage N2 larynx was commonest site of involvement. Bangladesh J Otorhinolaryngol; April 2015; 21(1): 17-22